Mimetic theory and film - Bubbio, Paolo Diego; Fleming, Chris (Violence, desire, and the sacred, 2019)
Intro -- Title Page -- Copyright Page -- Contents -- Notes on Editors and Contributors -- Introduction -- Notes -- Chapter 1: Buñuel's Apocalypse Now -- Notes -- Chapter 2: On Fiction and Truth: Joshua Oppenheimer's The Act of Killing -- But that is the Truth! -- Mimesis as reenactment and the voice of the victims -- Blindness and truth -- Silence -- Notes -- Chapter 3: Passing "The Imitation Game": Ex Machina, the Ethical, and Mimetic Theory -- Passing the Turing test -- The Imitation Game and Ex Machina -- The mimetic and the ethical -- Part four: The ethical, the mimetic, and Ex Machina -- Conclusion -- Notes -- Chapter 4: Femina ex machina -- Notes -- Chapter 5: Looking for a Scapegoat and Finding Oneself: Kieślowski's Decalogue and Mimetic Theory -- Decalogue One -- Decalogue Ten -- Conclusion -- Notes -- Chapter 6: Violence and Politics in Shakespeare's Macbeth and Kurosawa's Throne of Blood -- Notes -- Chapter 7: The Screenic Age -- Scene and screen -- Gilles Deleuze's two eras -- Notes -- Chapter 8: A Sacrificial Crisis Not Far Away: Star Wars as a Genuinely Modern Mythology -- "There is no escape"!: The original trilogy beyond the monomyth -- "The Sith and the Jedi are similar in almost every way": The prequels and the history of mythology -- "I have a bad feeling about this": The Sacrificial Crisis in the New Episodes -- Notes -- Chapter 9: Mimetic Magic and Anti-Sacrificial Slayage: A Girardian Reading of Buffy the Vampire Slayer -- The spell of desire -- Welcoming Dawn -- The dream reveals the reality -- Notes -- Chapter 10: It's Not the End of the World: Postapocalyptic Flourishing in Cartoon Network's Adventure Time -- The Utopian Dystopic Land of Ooo -- "Alright, I'll try to turn into a cheetah farting. I can't do the spots": Adventure Time on Mimesis, Desire, and Balbaflonic Lasers